2020
DOI: 10.1590/0103-8478cr20190445
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoid of the gallbladder in two dogs

Abstract: A carcinoid is a rare neoplasm derived from neuroendocrine cells that may arise in the hepatobiliary system. This report described two cases of carcinoid of the gallbladder in dogs, with emphasis on the clinical, pathological and immunohistochemical aspects. Case 1 was a 10-year-old female Shih Tzu, with a history of prostration and occasional episodes of diarrhea and vomiting. Case 2 was a 10-year-old male Cocker Spaniel, with a history of diarrhea and abdominal pain. Abdominal ultrasonography suggested a neo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…3,4 The intrahepatic and extrahepatic biliary ductal forms have been reported with much higher frequency in dogs and cats than the extrahepatic gallbladder form (herein referred to as GB-NEC). 1,2,4,5 To the authors' knowledge, the cytologic appearance of GB-NECs has not been reported. In this case, cytologic features, including indistinct intercellular junctions, acinar formations, and bare nuclei, were suggestive of NEC, and positive staining with synaptophysin supported the diagnosis.…”
Section: Discussionmentioning
confidence: 90%
“…3,4 The intrahepatic and extrahepatic biliary ductal forms have been reported with much higher frequency in dogs and cats than the extrahepatic gallbladder form (herein referred to as GB-NEC). 1,2,4,5 To the authors' knowledge, the cytologic appearance of GB-NECs has not been reported. In this case, cytologic features, including indistinct intercellular junctions, acinar formations, and bare nuclei, were suggestive of NEC, and positive staining with synaptophysin supported the diagnosis.…”
Section: Discussionmentioning
confidence: 90%
“…Reagents were manually applied and immunoreactivity was visualized by incubating the slides with diaminobenzidine chromogen (DAB Substrate System, Dako, Carpinteria, CA, USA) for 3 min. Details of the antibodies against Synaptophysin (1,22,23), NSE (22,24), CD56 (24), PGP 9.5 (25,26), Chromogranin A (25,27), Estrogen Receptor -RE (28), Progesterone Receptor -PR (29), Pancitokeratin (22) and Ki67 (30), dilutions, antigen retrieval procedures and incubation times used in the immunostaining process are shown in Table 1. Normal canine mammary gland was used as an internal positive control for Estrogen and Progesterone Receptors and Pancitokeratin.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…3 Clinical signs of carcinoid tumours arising from the gall bladder are non-specific, including anorexia, ascites, weight loss, diarrhoea, jaundice, vomiting, abdominalgia and haematemesis. 7,8 Haemobilia and haemocholecyst due to bleeding from carcinoid tumours have been reported in rare cases. 2 It is difficult to diagnose bleeding from carcinoid tumours before surgical exploration.…”
Section: Introductionmentioning
confidence: 99%
“…Primary carcinoid tumours arising from the gall bladder are considered slow growing, and affected animals have a good prognosis if metastasis to the other organs has not occurred 3 . Clinical signs of carcinoid tumours arising from the gall bladder are non‐specific, including anorexia, ascites, weight loss, diarrhoea, jaundice, vomiting, abdominalgia and haematemesis 7,8 . Haemobilia and haemocholecyst due to bleeding from carcinoid tumours have been reported in rare cases 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation